EFEK SAMPING LAMA APLIKASI DARI BLEACHING AGENT HIDROGEN PEROKSIDA 40% TERHADAP KEKASARAN PERMUKAAN RESIN KOMPOSIT TIPE NANOFIL - , IZFAN YULVIANSYAH, Dr.drg. Widjijono, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bleaching is a dental treatment uses chemical on discolored vital and nonvital teeth. From many bleaching techniques, there is one name in office bleaching which performed in the dentist's office. Often, the application of bleaching agents does not only touch the healthy tooth tissue, yet it has the potential to touch the tooth tissue that has tooth restoration, for example is the nanofill composite resin. The purpose of this study is to determine the adverse effects of application time of bleaching agent 40% of hydrogen peroxide on the surface roughness of nanofill type composite resin restorations. The study was conducted by an experimental laboratory method. The sample was a nanofill composite resin sample (Filtek Z350, 3M, USA) discshaped with a diameter of 10 mm and a height of 2 mm. Samples were made with a total of 12 samples, which were divided into 3 treatment groups with each group consist of 4 samples. The samples was soaked in aquades and put into incubator for 24 hours at 37OC. The samples applied with bleaching agent 40% hydrogen peroxide (Opalescense Boost, USA) at room temperature (25OC). Each treatment group had a different variation of contact time with bleaching agent, which were: 30 minutes, 45 minutes, and 60 minutes. The surface roughness was measured before and after the application of bleaching agent. Then the data delta (Î) of surface roughness were statistically analyzed using One-Way ANOVA followed by LSD0,05 significance test. Results showed the mean and standard deviation of delta (Î) of the initial and final surface roughness of nanofill composite resin with 30 minutes of contact time was 0.040 Â±0.016 ðm